2020
DOI: 10.1108/mabr-03-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential cruisers behavior based on a preference model: the Japanese cruise market

Abstract: Purpose The purpose of this study is to analyze the preferences of potential Japanese cruise ship tourists and identify the factors influencing their participation in cruise ship tourism. In the analysis, preference for cruise ports in East Asia is also examined. Design/methodology/approach The behavioral model of potential cruiser is developed through a mixed ordered logit approach. The data are collected by means of the stated preference method with the application of a Web-based questionnaire. Multiple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In order to minimize any possible bias, we may conduct a large-scale data collection in different cities in China so that we can generalize our study in the forthcoming years. Finally, we may investigate potential cruisers’ behavior on the basis of a preference model in the Chinese cruise market in a future study as we found that few studies have been undertaken in cruise tourism ( Kawasaki and Lau, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to minimize any possible bias, we may conduct a large-scale data collection in different cities in China so that we can generalize our study in the forthcoming years. Finally, we may investigate potential cruisers’ behavior on the basis of a preference model in the Chinese cruise market in a future study as we found that few studies have been undertaken in cruise tourism ( Kawasaki and Lau, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies on the motivations of cruise ship tourists have a strong regional bias, focusing mainly on tourists from regions in which the cruise tourism industry is more developed (e.g., North America, the Mediterranean, the Caribbean, Northern Europe, Singapore, and Australia). Only a small number of studies consider emerging cruise travel markets (e.g., Fan et al, 2015 ; Lemmetyinen et al, 2016 ; Sun et al, 2018 ; Kawasaki and Lau, 2020 ). Extant studies have found that cruise tourists’ travel motivations vary by region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seaborne transport is the most energy-efficient mode of transportation, and it forms the backbone of international trade and global supply chains (Christiansen et al, 2004;Kawasaki and Lau, 2020). According to the United Nations Conference on Trade and Development (UNCTAD), more than three fourths of merchandise traded globally by volume is carried by sea (UNCTAD, 2019).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Findings show that self-drive visitors (visitors who drive on routes for tourism) value the availability of road facilities (Wu et al, 2018), roadside facilities (Denstadli & Jacobsen, 2011), and scenery (Wu et al, 2018) on the route as important determinants of tourism satisfaction. Similarly, cruise tourists were found to consider the duration and cost of cruising (Kawasaki & Lau, 2020), the facilities available onboard (such as Wi-Fi, currency exchange, and shopping) (Di Vaio et al, 2021), and crowding in the cruise (Sanz-Blas et al, 2019) as influencers of cruising satisfaction and loyalty. Overall, managers of 'transport as tourism' destinations acknowledge the significant role of transportation facilities, services, and experiences for sustained and repeated tourism and put forward their efforts in investing in transportation facilities and services to improve visitors' transportation experience.…”
Section: Role Of Transportation Services and Experiences In Tourismmentioning
confidence: 99%